Finding France in Australia : your guide to finding everything essentially French right here in Australia - Matheson, Sally (South Yarra, Victoria : Matheson Publishing, 2017)
“Do you yearn for all things French – yet live in Australia? Here is your must-have guide to finding everything (almost everything) you have about France right here in Australia.”--Back cover.
Includes index.
Keywords: French -- Cultural assimilation -- Australia; French -- Australia; French restaurants -- Australia -- Directories; Popular culture -- France; Lifestyle, Hobbies & Leisure; Travel & holiday; France -- Guidebooks; Australian